Introducing Peer-supported Open Dialogue in changing mental health care - Lorenz-Artz, Karin; Bierbooms, Joyce; Bongers, Inge (Frontiers in Psychology, 2023)
The need to transform mental health care toward person-centered, recovery-based, and network-oriented care is recognized worldwide. Open Dialogue (OD) is seen as a hopeful approach in the context of this transformation and is introduced in countries around the globe. Five Dutch mental health care organizations spread over the Netherlands introduced the Peer-supported Open Dialogue (POD) approach, which adds an explicit role of peer-support workers to the OD approach. It appeared that (P)OD-trained professionals face issues in introducing the (P)OD approach in existing MHC settings. One of the reasons, which is the focus of this study, may be that they encounter difficulties in explaining to non-(P)OD-trained professionals what (P)OD entails. The main objective of this study is to provide guidance to and contribute to making (P)OD better understandable for non-(P)OD-trained professionals. In this study, we used a qualitative design and conducted 23 semi-structured interviews with POD-trained professionals with various backgrounds, to cultivate a rich understanding of which aspects could contribute to a better understanding of POD for non-POD-trained professionals. We used a hybrid approach to analyze the data, meaning that the technique of both inductive and deductive thematic analyses has been applied. From these analyses, six aspects emerged that could give guidance to and contribute to making (P)OD more understandable for non-(P)OD-trained professionals: (1) Experiencing (P)OD by attending treatment network sessions, (2) a coherent and profound narrative about (P)OD, (3) adjusting terminology to better fit the context, such as the two terms “principles” and “responsibility” in this study, (4) the order in which (P)OD elements are introduced in the narrative, (5) bringing the elements “presence,” “reflecting,” and “expertise by experience” more to the foreground, and (6) conceptualizing the main elements in a “talking paper.” A better understanding of (P)OD might be one of the building blocks for improving (P)OD adoption in existing MHC practices, which are on their way toward person-centered, recovery-based, and network-oriented care.